Implementation of the MDLC Method in Designing 2D Animation About Menstruation for Adolescent Girl - Bayu Syahputra; Deli Deli; Christine Gabriella (Universitas Internasional Batam, 2024)
Puberty in teenage girls is usually marked by menarche or first menstruation. There are several factors that cause abnormal menstrual cycles such as stress, nutritional problems, hormonal disorders and also chronic diseases. Knowledge and insight about menstruation is very important in the growth and development of a woman. By designing a 2D animated video about menstruation, we can provide information to young women. The method that will be used for data collection is by interviewing experts in the field and the method used in designing 2D animation video is MDLC (Multimedia Development Life Cycle). The result of this research is a 2D animated video entitled